The art of RF (Riba-Free) Islamic banking and finance: tools and techniques for community-based banking - Abdul-Rahman, Yahia, 1944- (Hoboken, New Jersey : Wiley, 2014)
'Updated and expanded insights into Islamic banking and financeFrom Yahia Abdul-Rahman-the father of Riba-Free (RF) banking-comes the expanded edition of the definitive resource that offers an understanding for applying Islamic banking and financial practices. No matter what your faith or religious beliefs, the book shows how to take a modern American approach to incorporating Islamic financial principles into banking and investment techniques.The Art of Islamic Banking and Finance describes the emergence of a culture of Islamic banking and finance today, which is based on the real Judeo-Christian-Islamic spirit and has proven very effective when compared to 20th century models that use financial engineering and structural techniques to circumvent the Shari'aa Law. The author also reveals information about how fiat money is created, the role of the Federal Reserve, and the US banking system. Abdul-Rahman includes a wealth of real-life examples and offers an analysis of how this new brand of banking and financing yields superior results. Offers the fundamentals on Riba-Free (RF) banking Shows how to apply RF to everything from joint ventures and portfolio management to home mortgages and personal finance Reveals what it takes to incorporate Shariah Law into US financial systems Includes information on why RF banking is a socially responsible way to invest Thoroughly revised and updated, this resource offers a handbook for applying Shari'aa law to American banking and finance'--
'This book explains the application of Shari'aa law to American banking and finance. The book describes the fundamentals of Riba-Free (RF) banking; shows how to apply RF to everything from joint ventures and portfolio management to home mortgages and personal finance; reveals what it takes to incorporate Shariah Law into US financial systems; and includes information on why RF banking is a socially responsible way to invest'--
Includes index.
First Edition of this book was published by John Wiley & Sons, Inc. in 2010.
Includes bibliographical references and index.
Keywords: Banks and banking -- Islamic countries; Banks and banking -- Religious aspects -- Islam; Finance -- Islamic countries; Finance -- Religious aspects -- Islam